Liposomes as a model for the study of high frequency dielectrophoresis. Issue 13 (18th May 2015) - Hadady, Hanieh; Montiel, Caroline; Wetta, Daniel; Geiger, Emil J.; Lapizco‐Encinas, Blanca H.
<x xml:space="preserve">Abstract</x> Liposomes were used as a physical model to study the dielectrophoretic response of single‐shelled particles at high frequencies. For a typical particle, the single‐shelled theoretical model predicts a lower cross‐over frequency that depends upon the dielectric properties of the shell and an upper crossover frequency that depends upon the dielectric properties of the interior. Dried liposomes were rehydrated in media with conductivity ranging from 100 to 2000 μS/cm. The high frequency dielectrophoresis response of the liposomes was observed in the range of 1–80 MHz at 30 volts peak‐to‐peak, and the upper cross‐over frequency was recorded. The experimental results closely matched the theoretical expectations. In particular, the upper cross‐over frequency ranged from 9 to 60 MHz and was found to depend linearly on the interior conductivity of the liposome. These results further confirm the single‐shell model at high‐frequencies. Moreover, they suggest liposomes may be a useful model particle for use during the development of dielectrophoresis‐based devices.